Fomenting Sickness: Nocebo Priming of Residents about Expected Wind Turbine Health Harms - Chapman, Simon; Joshi, Ketan; Fry, Luke (Frontiers in Public Health, 2014)
A nocebo effect hypothesis has been proposed to explain the varying spatio-temporal distribution of reported complaints by small minorities of exposed residents about noise and health effects said to be caused by wind farm turbines. The hypothesis requires that those complaining have been exposed to negative, potentially frightening information about the impact of proposed wind farms on nearby residents, and that this information conditions both expectations about future health impacts or the aetiology of current health problems where wind farms are already operational. This hypothesis has been demonstrated experimentally under laboratory conditions, but case studies of how this process can operate in local communities are lacking. In this paper we present a case study of the apparent impact of an anti wind farm public meeting on the generation of negative news media and the subsequent expression of concerns about anticipated health and noise to a planning authority approval hearing in Victoria, Australia. We present a content analysis of the negative claims disseminated about health and noise in the news media and available on the internet prior to the hearing, and another content analysis of all submissions made to the planning authority by those opposing the development application.